Dinâmicas de abastecimento nos sistemas alimentares em Belo Horizonte - Melissa Luciana de Araújo; Milene Cristine Pessoa; Olivia Souza Honório; Maycon Noremberg Schubert; Sergio Schneider; Catia Grisa (Confins)
This paper analyzes the historical transformations and recent dynamics of food supply in Belo Horizonte and associates these dynamics with different configurations of food systems (modern, mixed and traditional). The study mobilizes different research techniques and data sources, prevailing documentary research, literature review, and secondary data survey. The results show major transformations in the dynamics of food supply in the municipality throughout the 20th century, with food and elements associated with modern food systems gaining relevance. In fact, nowadays the presence of retail trade stands out, followed by specialized food companies and wholesale trade, which are fundamentally linked to mixed and modern food systems. These dynamics are permeated, to a lesser extent, by public policies for commercialization and access to food, which are fundamentally linked to mixed and traditional food systems. The analysis shows the existence of a variety of food systems and environments in Belo Horizonte, which pose different challenges for building healthier, more inclusive and sustainable food dynamics.